ADI, ASIS, ASIS&T"¦, trends and opportunities for professional networking - Ortiz-Repiso, Virginia; Cobarsí-Morales, Josep (Anuario ThinkEPI, 2017)
A brief review of ASIS&T and its historical evolution over the course of 80 years is carried out, beginning with its founding as the American association of documentation to its current reality as an international association, which is a leader in the field of information and related technologies. Its three main structures, where affiliates may work according their situation and needs, are described: stakeholder groups, regional chapters, and chapters of students. The resources and existing publications are described, some of which are exclusive to affiliates, while others are open to the general public. Finally, the main advantages of belonging to the Association are revealed, with special emphasis on aspects of mentoring and networking.